Design recommendations for the creation of icons for the elderly. - Soares, Marcelo M.; Jacobs, Karen; Mertens, Alexander; Brandl, Christopher; Przybysz, Philipp; Koch-Körfges, David; Schlick, Christopher M. (Work)
During employment of icons in order to represent system functions, specific user requirements from elderly people have not been scientifically gathered and thus will merely be considered during the process of system design. The survey, with explicit consideration of technology acceptance and experience of 120 elderly probands, looked into the comprehension of four different classes of non-animated graphical representations. It was shown that among elderly, the use of photos compared to pictograms or clip art leads to a significantly higher recognition rate. The mapping of actions rather than objects leads to a further reduction of the error probability and is thus, especially in the context of telemedicine, preferable for the target group.